Development of LKS Based on Contextual Approach to Improve Students' Mathematical Communication Ability on Statistics Material Class VII Junior High School - Rosmaiyadi, Rosmaiyadi; Utami, Citra; Dale, Aldi Fandry; Buyung, Buyung; Husna, Nurul (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This study aims to develop LKS based on a contextual approach that meets the criteria of valid, practical, and effective in improving students' mathematical communication skills in class VII junior high school statistics material. The validity analysis is based on data from the LKS validation results by validators, the practicality analysis is based on data from student and teacher response questionnaires and observations of learning implementation, and the effectiveness analysis is based on data from student mathematical communication ability test results. The LKS development model refers to the 4-D model (Four D Model) which is modified without using the Desseminate stage into a 3-D model (Three D Model) namely Define, Design, and Develop and using the One Group Pre-test Post-test Design research design. The research subjects were VII grade students of SMP Torsina II Singkawang, namely 1 experimental class totaling 34 students. The results of the research obtained are 1) The results of the LKS validation by the validator show an average score of 4.17 with good criteria, which means that the LKS meets the valid criteria. 2) The results of the student response questionnaire show an average percentage of 94% with very good criteria, the results of the teacher response questionnaire show an average percentage of 88% with very good criteria, and the observation of learning implementation shows an average percentage of 96% with very good criteria, which means that the LKS meets practical criteria. 3) The results of the mathematical communication ability test showed that the students who reached the 70 KKM score individually were 29 students out of 34 students and the proportion of students reaching the KKM classically was 75%, which means that the LKS meets the effective criteria.